Gastric and intestinal myiasis due to Ornidia obesa (Diptera: Syrphidae) in humans. First report in colombia (2023)
Myasis are parasitic infestations of animals and humans tissues and is caused by fly larvae. This kind of infestation has Public Health importance. In the Colombian biomedical literature the reports about myiasis in humans are scarce. In this paper, we report two cases of patients with gastrointestinal myiasis where the etiologic agents involved were Ornidia obesa and Ornidia sp (Diptera: Syrphidae). The taxonomic identification of the larvae was done at the Colombian Institute of Tropical Medicine and taxonomic confirmation was done at the laboratory of medicine veterinary and Zoology of Sao Pablo University. These two cases of myiasis are of first report in Colombia.